Vertical profile of culturable bacteria from the Makassar Strait, Indonesia - ZEN LADESTAM SIALLAGAN; TATI KRISTIANTI; FENNY MARTHA DWIVANY; HUSNA NUGRAHAPRAJA; CHARLIE ESTER DE FRETES; MUHAMMAD FADLI; JOKO PEBRIANTO TRINUGROHO; OCKY KARNA RADJASA; R. DWI SUSANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Siallagan ZL, Kristianti T, Dwivany FM, Nugrahapraja H, Fretes CED, Fadli M, Trinugroho JP, Radjasa OK, Susanto RD. 2023. Vertical profile of culturable bacteria from the Makassar Strait, Indonesia. Biodiversitas 24: 1356-1365. Indonesia's extensive maritime background is a rich biological and chemical diversity source. This diversity has become as source of unique chemical compounds with the potential for industrial development as enzymes, molecular probes, chemicals, pharmaceuticals, cosmetics, nutritional supplements, and agrochemicals. The present study aimed to analyze the community composition of culturable bacteria from three different layers of depth from Makassar Strait using high throughput DNA Illumina sequencing of 16S rRNA. Bioinformatic analysis has rendered 140336 high-quality sequences with an average of 124127 sequences per sample and a mean read length of 428 bp. Results showed that Firmicutes and Proteobacteria were the two most abundant phyla. Taxonomic analysis showed that Firmicutes dominated all samples. Genus Streptomycetes and Psychrobacter occurred mainly in the culture from the surface layer. Species richness and diversity for the bacterial communities at 100 m were higher than those at 5 m and 200 m. PCA plot, NMDS plot, and UPGMA clustering demonstrated that the culturable bacterial community compositions of 100 and 200 ms were highly similar and distinct from those in 5 m. This research discovered microbes with potential as sources of marine natural products, including Streptomyces, Paenibacillus, Bacillus, Psychrobacter, Arthrobacter, Bradyrhizobium, Gemmatimonas, and Acidobacteria.